2015
DOI: 10.1007/s00436-015-4560-6
|View full text |Cite
|
Sign up to set email alerts
|

Tsetse diversity and abundance in Southern Burkina Faso in relation with the vegetation

Abstract: The increase of human population, combined with climatic changes, contributed to the modification of spatial distribution of tsetse flies, main vector of trypanosomiasis. In order to establish and compare tsetse presence and their relationship with vegetation, entomological survey was performed using biconical traps deployed in transects, simultaneously with phyto-sociological study, on the Comoe river at its source in the village of Moussodougou, and in the semi-protected area of Folonzo, both localities in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
5
1
2
Order By: Relevance
“…However, an animal origin could also be suspected due to the massive cattle transhumance between the Ivorian foci and the Banfora area that is still tsetse infested [5]. This last case confirmed that there is still a risk of HAT re-emergence in areas where the vector persists in Burkina Faso, mainly in the southwestern part of the country [3,8,9]. This justified the implementation of HAT passive surveillance in this area [5].…”
Section: Introductionmentioning
confidence: 76%
“…However, an animal origin could also be suspected due to the massive cattle transhumance between the Ivorian foci and the Banfora area that is still tsetse infested [5]. This last case confirmed that there is still a risk of HAT re-emergence in areas where the vector persists in Burkina Faso, mainly in the southwestern part of the country [3,8,9]. This justified the implementation of HAT passive surveillance in this area [5].…”
Section: Introductionmentioning
confidence: 76%
“…Studies on the vegetation composition showed that the riparian forest (gallery) was conserved along the riverbank. The most important species in the riparian forest in terms of abundance were: Dialium guineense , Syzygium guineense , Manilkara multinervis , Morelia senegalensis , Cola laurifolia, Berlinia grandiflora and Mitragyna inermis (Rayaisse et al ., ). Glossina tachinoides coexists in sympatry with G. palpalis gambiensis (Amsler et al ., ; Rayaissé et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The last dataset from Burkina Faso are from a recent study in the southern party of the country where entomological surveys were conducted in Moussodougou and Folonzo [ 24 ]. In these surveys, 25 traps were deployed in each site for 5 days during the rainy and dry seasons 2011–2012.…”
Section: Methodsmentioning
confidence: 99%